Foliar Application of Biostimulant Mitigates Water Stress Effects on Soybean - Gabriel Bressiane Melo; Alessandro Guerra da Silva; Alan Carlos da Costa; Adnan Alves da Silva; Márcio Rosa; Layara Alexandre Bessa; Carlos Ribeiro Rodrigues; Gustavo Castoldi; Luciana Cristina Vitorino (Agronomy, 2024)
Climate change has emerged as a challenge for soybean cultivation around the world, stimulating the development of technological alternatives that aim to mitigate the damage caused by water deficit. From this perspective, algae extract-based biostimulants have been tested to reduce water stress in several crops, but little is known about their effects on soybean. Thus, we hypothesize that a commercial biostimulant based on Ascophyllum nodosum can improve the physiological performance and water relations of Glycine max plants subjected to water deficit. To test this hypothesis, we set up an experiment in controlled conditions in a greenhouse, considering five treatments (control; application of biostimulant; water deficit (WD); WD + application of biostimulant; and WD + split application of biostimulant). The experiment was designed in completely randomized blocks with four replications per treatment and conducted in polyethylene pots containing 10 L of soil and three plants per pot. The irrigation was carried out daily; the water deficit was 50% soil moisture at field capacity, starting at the R1 stage (beginning of flowering, where there is at least one flower open at any node on the plant) and maintained for ten days. The biostimulant was applied concurrently with the onset of water deficit. We confirmed the hypothesis that foliar application of 1.0 L ha−1 of the biostimulant reduces the deleterious effects of the common water deficit at the beginning of the reproductive stage of soybean through the reduction of damage from oxidative stress (reduction of malondialdehyde synthesis by 31.2% in relation to the WD plants), maintenance of water potential and cellular homeostasis (10.2% increase in relative water content when compared with WD plants), and conservation of the contents of chlorophyll in leaves and stimulation of photosynthesis and carboxylation (68% increase in net photosynthetic rate and 49.3% increase in carboxylation efficiency in relation to WD plants). However, when applied in installments, the biostimulant was not efficient in reducing soybean water stress. Therefore, we conclude that the application of a biostimulant based on A. nodosum can help reduce the harmful effects of water deficit on soybean plants, opening up perspectives for the mass use of this extract in agricultural crops produced on a large scale.